2011
DOI: 10.1309/ajcp4vfka5fcmzna
|View full text |Cite
|
Sign up to set email alerts
|

A Multisite Performance Study Comparing the Reading of Immunohistochemical Slides on a Computer Monitor With Conventional Manual Microscopy for Estrogen and Progesterone Receptor Analysis

Abstract: A multisite study was conducted to assess the performance of the Aperio digital pathology system (Aperio Technologies, Vista, CA) for reading estrogen receptor (ER) and progesterone receptor (PR) slides on a computer monitor. A total of 520 formalin-fixed breast tissue specimens were assayed at 3 clinical sites for ER and PR (260 each). Percentage and average staining intensity of positive nuclei were assessed. At each site, 3 pathologists performed a blinded reading of the glass slides using their microscopes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
1
11
0
1
Order By: Relevance
“…[24] There is also considerable importance given to reproducibility of results to insure that this expensive therapy is given to those patients who are most likely to benefit from its use. Although multiple prior studies of immunohistochemical stains in general,[52526] and more specifically HER2 studies have shown substantial agreement between glass slide and digital interpretations,[679111227] studies of automated image analysis algorithms on HER2 interpretation comparing different scanning devices and different image analysis algorithms have suggested that there may be differences between the instruments and hence that verification of each individual system's performance should be accomplished prior to clinical use. [10] Individual laboratories that use these FDA cleared devices do not have to repeat the studies presented herein, but do have to perform verification procedures to insure that the device/system is performing at its expected level.…”
Section: Resultsmentioning
confidence: 99%
“…[24] There is also considerable importance given to reproducibility of results to insure that this expensive therapy is given to those patients who are most likely to benefit from its use. Although multiple prior studies of immunohistochemical stains in general,[52526] and more specifically HER2 studies have shown substantial agreement between glass slide and digital interpretations,[679111227] studies of automated image analysis algorithms on HER2 interpretation comparing different scanning devices and different image analysis algorithms have suggested that there may be differences between the instruments and hence that verification of each individual system's performance should be accomplished prior to clinical use. [10] Individual laboratories that use these FDA cleared devices do not have to repeat the studies presented herein, but do have to perform verification procedures to insure that the device/system is performing at its expected level.…”
Section: Resultsmentioning
confidence: 99%
“…These diagnostic algorithms facilitate quantification of IHC positivity resulting in a more objective evaluation, which is extremely useful in the evaluation of some biological markers. Algorithms for the evaluation of IHC stains are variably used depending on the subspecialties and are particularly useful in cases of breast cancer [26,27,28,29]. …”
Section: Advantages and Challenges Of Wsi For Routine Diagnosismentioning
confidence: 99%
“…A major advantage of digitization in breast pathology is the possibility to use image analysis to improve the accuracy and reproducibility of HER-2, estrogen and progesterone receptors, and Ki67 scoring, which have a crucial role in the planning of treatment strategies [27,28,29,49]. Moreover, the evaluation may be improved with the use of automatic quantification algorithms (fig.…”
Section: Breast Pathologymentioning
confidence: 99%
“…La microscopie digitale permet la normalisation de la numĂ©risation et l'affichage des images microscopiques sur un Ă©cran d'ordinateur. La microscopie digitale amĂ©liore la prĂ©cision, la fiabilitĂ© et la reproductibilitĂ© de la quantification immunohistochimique en mettant en Ă©vidence les erreurs possibles d'interprĂ©tation en microscopie manuelle [2]. Les images numĂ©riques ont aussi l'avantage de faciliter le stockage, la rĂ©cupĂ©ra-tion et le partage entre pathologistes, ce qui amĂ©liore la consultation des donnĂ©es.…”
Section: Les Lames Virtuelles : Un Champ D'application Immense En Recunclassified